Neuropsychological Functioning among Chronic Khat Users in Jazan Region, Saudi Arabia. Issue 3 (July 2014) - Ismail, Ahmed A.; El Sanosy, Rashad M.; Rohlman, Diane S.; El-Setouhy, Maged
Background: Khat chewing effects in the central nervous system are attributed to cathinone and cathine, which are structurally related to amphetamine. However, studies on neuropsychological problems arising from khat use in humans are not extensive and have only included observational and single-case studies. The aims of this study were to (1) to examine neuropsychological functions among khat chewers, and (2) to determine factors affecting neuropsychological outcomes among khat chewers. Methods: A sample of 70 adult male khat chewers and a control group of 72 nonchewers were recruited from the Jazan region in southwest Saudi Arabia. A questionnaire examining socioeconomic background, medical and occupational history, education, and khat chewing behaviors was administered. Neuropsychological performance was assessed using computerized tests from the Behavioral Assessment and Research System (BARS) that assessed learning, episodic and working memory, motor speed/coordination, attention/information processing speed, sustained attention, set-shifting/response inhibition, and perceptual functions; noncomputerized tests, Trail Making A and B, Block Design, and Benton Visual Retention tests were also administered. Results: Khat chewers performed significantly worse on 3 out of 14 neuropsychological subtests compared with the control group, representing learning, motor speed/coordination, and set-shifting/response inhibition functions. Age and educational level were identified as predictors of neuropsychological outcomes of khat chewers. Conclusions: The chronic chewing of khat leaves is associated with deficits in some neuropsychological functions, which may affect the mental and neurological health of communities in which khat chewing is a common habit.